2019
DOI: 10.1002/path.5278
|View full text |Cite
|
Sign up to set email alerts
|

Prosaposin is a biomarker of mesenchymal glioblastoma and regulates mesenchymal transition through the TGF‐β1/Smad signaling pathway

Abstract: Mesenchymal glioblastoma (GBM) is the most aggressive subtype of GBM. Our previous study found that neurotrophic factor prosaposin (PSAP) is highly expressed and secreted in glioma and can promote the growth of glioma. The role of PSAP in mesenchymal GBM is still unclear. In this study, bioinformatic analysis, western blotting and RT‐qPCR were used to detect the expression of PSAP in different GBM subtypes. Human glioma cell lines and patient‐derived glioma stem cells were studied in vitro and in vivo, reveali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…Additionally, immunofluorescence also showed that FTY720 treatment significantly inhibited EMT in sacrum chordoma cells. EMT is a common phenomenon in epithelial-derived malignant tumours and is responsible for invasion and radiotherapeutic and chemotherapeutic tolerance of malignant tumours [39][40][41]. Our findings suggest that FTY720 treatment inhibited the invasion of chordoma cells and enhanced the effects of radiotherapy and chemotherapy by altering EMT.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, immunofluorescence also showed that FTY720 treatment significantly inhibited EMT in sacrum chordoma cells. EMT is a common phenomenon in epithelial-derived malignant tumours and is responsible for invasion and radiotherapeutic and chemotherapeutic tolerance of malignant tumours [39][40][41]. Our findings suggest that FTY720 treatment inhibited the invasion of chordoma cells and enhanced the effects of radiotherapy and chemotherapy by altering EMT.…”
Section: Discussionmentioning
confidence: 58%
“…PSAP is a highly conserved glycoprotein and precursor of lysosomal proteins (saposins A–D) that is integral to the intracellular degradation of sphingolipids [ 64 ]. Previously, we showed that PSAP levels in GBM-EVs have a significant, positive correlation to in vitro GBM cell invasion [ 29 ] and multiple studies have reported high PSAP expression in clinical glioma specimens, glioma-stem cells and cell-lines [ 65 , 66 ]. PSAP was not confidently identified in EVs captured directly from diffuse glioma (II–IV) microenvironments [ 24 , 25 ], and here we report significantly lower PSAP levels in GBM plasma-EVs relative to controls.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a key event driving the invasion of glioma cells [43,44]. In addition, several EMT-related factors are associated with increased invasion and poor prognosis in gliomas [45][46][47]. Here, we observed that CUL7 depletion significantly reversed EMT features and decreased invasiveness in glioma cells.…”
Section: Discussionmentioning
confidence: 57%